Exercise Improves Academic Performance - Cappelen, Alexander W.; Charness, Gary; Ekström, Mathias; Gneezy, Uri; Tungodden, Bertil (Journal of Political Economy, 2026)
In a randomized controlled trial, we test whether removal of a barrier to exercise can improve academic performance.We find strong support for this hypothesis: university students who were provided with a free gym card exercised more and had a significant improvement in academic performance.The treated students were both less likely to drop out of classes and to fail at the exam.We provide evidence showing that exercise caused a healthier lifestyle and increased perceived self-control, which ultimately improved academic performance.The study demonstrates that removing barriers to physical activity can be an important tool for improving educational achievements.